Developing of Literacy Skills in Writing Stories for Elementary School by Using Big Book - Zainuddin, Mohammad; Saifudin, Ahmad; Lestariningsih, Lestariningsih; Nahdiyah, Umi (Jurnal Prima Edukasia, 2023)
The aim of this study is to describe the process and the result of developing literacy skills in writing stories for Elementary School by Using Big Book. This study uses research and development research methods. The steps taken from the ADDIE development model were used in this research's research model for the development of teaching and learning media, which included five stages, namely (analysis), (design), (development), (implementation), and (evaluation). The subjects of the preliminary field test were grades 4, 5, and 6 using the random sampling method. The research data was obtained through the interview technique which was conducted after the observation process of classroom learning within a period of 3 months of classroom learning. The data was collected by observation, interviews, product validation, and questionnaires. The results of this study resulted in a Big Book-based thematic textbook product with the TPACK model that has been tested and validated by experts. The average results starting from the assessment of the feasibility of big book textbooks by material testing, feasibility of textbooks by media experts, feasibility of big book textbooks by classroom teachers, feasibility of big book textbooks by small group testing, and feasibility of big book textbooks by testing field obtained an average of 4.35. It means that the big book is very suitable to be used as a teaching medium in literacy learning for students of Wildan Mukholladun.